Site-directed mutagenesis of the COOH-terminal region of colicin A: effect on secretion and voltage-dependent channel activity. - Baty, D (1987)
A large number of mutants introducing point mutations and deletions into the COOH-terminal domain of colicin A have been constructed by using site-directed mutagenesis. The COOH-terminal domain carries the channel activity. The effects of the alterations in the polypeptide chain on the secretion of colicin A by colicinogenic cells have been investigated. All deletions and some mutations were found to lead to protein aggregation in the cytoplasm, thereby preventing release into the medium. The mutated colicin A proteins have been purified, and their activity in vivo (on sensitive cells) and in vitro (in planar lipid bilayers) has been assayed. Deletions in the region containing putative helices 4, 5, and 6 (predicted to be involved in pore formation) and the transitions (Ala----Asp-492, Phe----Pro-493) in helix 4 abolished the activity. No correlation was observed between mutations leading to protein aggregation and those leading to loss of channel activity. Some mutations were found to alter characteristic properties of the single channels, such as stability, current-relaxation kinetics, voltage dependence, and pore conductance. Site-directed mutagenesis provides a powerful tool for studying structure-function relationships of voltage-sensitive ionic channels.